Gas phase pyrolysis synthesis of carbon nanotubes at high temperature. (15th October 2017) - Hou, Guangfeng; Chauhan, Devika; Ng, Vianessa; Xu, Chenhao; Yin, Zhangzhang; Paine, Michael; Su, Ruitao; Shanov, Vesselin; Mast, David; Schulz, Mark; Liu, Yijun
Abstract: In this study, carbon nanotubes were synthesized at high temperature (1150–1500 °C) using the substrate-free gas phase pyrolysis method. The CNT sock morphology, CNT structure, impurity, process yield and growth efficiency at high temperatures were investigated. It was found that the CNTs transform from single-walled to multi-walled nanotubes at elevated temperature. The amount of amorphous impurities increases with higher temperature, possibly due to an increased non-catalytic decomposition of hydrocarbons. However the CNT quality increases, as indicated by a higher Raman spectroscopy IG /ID ratio. The process yield increase by two folds at higher temperature (1500 °C) compared to a lower temperature (1200 °C), but the catalyst efficiency is highest at 1400 °C with 1 g Fe producing 5.1 g CNT. The calculated carbon conversion rate is lower than 4%. The CNT growth is not limited by the availability of carbon around the catalyst, instead of by the availability of active catalyst particles. Based on a pristine CNT sheet, the measured electrical conductivity is highest at 1400 °C, due to a balance between impurities and CNT quality. The tensile strength of the CNT sheet increases with the temperature, possibly because of the "gluing" effect of the carbonaceous impurities. Graphical abstract: Highlights: High-temperature synthesis of CNTs in gas phase pyrolysis method has been investigated. The CNTs transform from single-walled to multi-walled, with an increase of amorphous impurities at elevated temperature. The CNT quality increases at higher temperature, indicated by a higher Raman IG /ID ratio. The catalyst efficiency is highest at 1400 °C with 1 g Fe producing 5.1 g CNT.